Factors Affecting the Mechanical Properties of Cement-Mixed Gravel - Chen Wang; Wentao Li (Advances in Materials Science and Engineering)
A study has been conducted to investigate the mechanical properties of cement-mixed gravel using the unconfined compression test and the tensile test. Basic factors including the curing period, the water-binder ratio, the cement content, and the strain rate were evaluated. Ordinary Portland cement with fly ash was employed as the cementation agent for preparing cemented samples. The results indicate that the unconfined compressive strength, the deformation modulus, and the tensile strength increase with the increase in the curing period. The ratio of tensile strength to unconfined compressive strength has no distinct change after 7 days. An optimum water-binder ratio can be obtained. The unconfined compressive strength and deformation modulus decrease as the water-binder ratio decreases and increase from the optimum water-binder ratio. With the increasing of the cement content, the unconfined compressive strength increases distinctly, the deformation modulus increases significantly when the cement content is less than 4% and then increased slowly, and the failure strain increases to a peak value and then decreases. With the increasing of the strain rate, the unconfined compressive strength increases slightly and the deformation modulus increases slowly. The failure strain decreases with an increase in the strain rate.